2023
DOI: 10.1111/pan.14767
|View full text |Cite
|
Sign up to set email alerts
|

A neonate with aseptic cutaneous necrosis related to the migration of the proximal central venous catheter infusion port

Gokul Thimmarayan,
Michael Schmitz,
Jorge Guerrero
et al.

Abstract: We report a case of aseptic cutaneous necrosis from extravasation of calcium chloride at the proximal port of a central venous catheter (CVC). A right internal jugular CVC was placed with ultrasound guidance using contemporary guidelines for size and insertion site. Catheter migration occurred concurrent with development of postoperative anasarca. Four days later, leakage of infusate with skin necrosis was noted at the insertion site. Despite initial proper positioning, catheter ports can migrate out of intrav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
2
0
0
Order By: Relevance
“…In an animal study, Taogoshi et al16 suggested that calcium chloride extravasation causes tissue necrosis and phlebitis, equating the properties of calcium chloride to those of vesicants in chemotherapy agents. Several case reports have described the occurrence of skin injuries due to the extravasation of calcium chloride 17,18. These fundamental and clinical findings support the results of this study, suggesting that severe skin injuries are more likely to occur with calcium chloride administration.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In an animal study, Taogoshi et al16 suggested that calcium chloride extravasation causes tissue necrosis and phlebitis, equating the properties of calcium chloride to those of vesicants in chemotherapy agents. Several case reports have described the occurrence of skin injuries due to the extravasation of calcium chloride 17,18. These fundamental and clinical findings support the results of this study, suggesting that severe skin injuries are more likely to occur with calcium chloride administration.…”
Section: Discussionsupporting
confidence: 89%
“…Several case reports have described the occurrence of skin injuries due to the extravasation of calcium chloride. 17,18 These fundamental and clinical findings support the results of this study, suggesting that severe skin injuries are more likely to occur with calcium chloride administration. Drugs classified as "cardiac therapy" in the ATC classification system were associated with severe skin injuries, with dopamine hydrochloride being the most common in this study.…”
Section: Drugssupporting
confidence: 81%